2006
DOI: 10.1212/01.wnl.0000216271.96364.50
|View full text |Cite
|
Sign up to set email alerts
|

Brain volume changes in CADASIL

Abstract: This study identifies brain atrophy as an important aspect of the disease process in CADASIL and establishes significant correlations with multiple clinical aspects including cognition. Age and systolic blood pressure are risk factors for brain volume loss during follow-up. Percent brain volume change seems promising as an adjunct outcome measure in future interventional trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
111
2
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(129 citation statements)
references
References 31 publications
14
111
2
2
Order By: Relevance
“…In contrast, age, male sex, and the volume of lacunar infarcts were found to be predictors of brain atrophy in line with results previously obtained in smaller samples of patients. 12,13 In the multivariate analysis, removing of confounders one by one showed that the positive association between brain parenchymal fraction and WMH remained unchanged as long as age was maintained in the model. This association is modest but highly significant and probably hidden at the crosssectional level by the strong but inverse effect of age on brain volume.…”
Section: Discussionmentioning
confidence: 98%
“…In contrast, age, male sex, and the volume of lacunar infarcts were found to be predictors of brain atrophy in line with results previously obtained in smaller samples of patients. 12,13 In the multivariate analysis, removing of confounders one by one showed that the positive association between brain parenchymal fraction and WMH remained unchanged as long as age was maintained in the model. This association is modest but highly significant and probably hidden at the crosssectional level by the strong but inverse effect of age on brain volume.…”
Section: Discussionmentioning
confidence: 98%
“…2,11 Brain parenchymal fraction (BPF), defined as the ratio of brain volume to the intracranial cavity volume, and the volume of lacunes were determined from the 3D-T1 sequence in all subjects. 12 Masks of lacunes were obtained manually by a trained rater. Hypointense lesions with a signal identical to that of CSF, sharp delineation, and a diameter of Ͼ2 mm were selected for this segmentation.…”
Section: Neuropsychological Assessmentmentioning
confidence: 99%
“…In the future, neurobiological markers of early injury will probably be used in studies trying to influence the onset and progression of clinical changes; this should help reducing the number of patients needed in therapeutic studies. The search for these markers in MR studies involving analysis of the patterns of appearance and progression of atrophy and accumulation of white matter lesions and other typical structural changes is under way, as well as analyses of diffusion histograms and metabolic relations as assessed by spectroscopy 89,[132][133][134][135] . The main marker of disease progression is, unfortunately, increasing age, which can be seen as a non modifiable risk factor.…”
Section: Treatment Of Cadasilmentioning
confidence: 99%